Assessment of climate change impact on land capability of the Makiling forest reserve - Salamante, Erlinda Encisa (1999)
A simulated soil erosion-based land capability classification was used in this study to assess the impact of climate change on the Makiling Forest Reserve, Philippines. The impact assessment was based primarily on the effect of rainfall change on the land capability of the study area. The simulated values of rainfall up to the year 2075, extracted from the GCMs of the global climate system, were used to represent climate change. These values were used as inputs to the USLE model to elucidate the information needed. The parameters, namely, rainfall, soil erodibility, slope length, slope steepness, land cover and management, and erosion control practices were incorporated/included in the USLE model. The data were processed and analyzed with the use of SAGE, a geographic information system software. Climate change was projected by comparing the result of the present land capability classification with that of the simulation result. Results showed that changes in rainfall (3 mm average monthly change) could greatly affect the land capability of MFR. More than 90% of the entire forest reserve was predicted to have an 'unacceptable' soil erosion by year 2075. The municipalities of Calamba, Laguna and Sto. Tomas, Batangas are the areas identified to suffer the most if the predicted climate change would prevail. From these results, amendments and creation of appropriate policies can be done for the sustainability of the MFR.
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman.
Keywords: Climatic changes -- Philippines -- Mount Makiling; Rainfall anomalies -- Philippines -- Mount Makiling; Soils and climate -- Philippines -- Mount Makiling